PERTUMBUHAN, PERUBAHAN, DAN PENGEMBANGAN MAHASISWA - Evaf Maulina (JURNAL MITRA MANAJEMEN, 2013)
AbstractThis paper argues for polices and practices to create higher education environmentsthat will faster broad-based development of human talent and potentials to our society inthe twenty first century. We believe that this orientation and resulting changes willrestore public confidence and political investment. Education and identity offer aframework for human development seven “vectors” such as developing competence,managing emotions, moving through autonomy toward interdependence, and othercritical to the needs of every college student. The college can strengthen developmentalong these vectors. They examine such as institutional objectives, size, curriculum,student programs and service, and student faculty relationship that contribute toeducationally powerful environments.